Eight below [videorecording (DVD)] - Marshall, Frank; Walker, Paul, 1973-2013; Greenwood, Bruce, 1956-; Bloodgood, Moon (Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
An American geologist flies to Antarctica to participate in a project at the United States Research Base. Once there, he teams up with arctic guide Jerry Shepard and his best friend, Cooper. The scientist soon discovers that Shepard also has eight other valuable friends -- a pack of sled dogs he's worked with for years, who have rescued him from a number of tight spots. As the three men explore a frozen mountain region, an unexpected accident coupled with a massive storm front forces them to fly to safety, leaving the dogs behind. Shepard is determined to rescue his canine friends, but he has to wait until the weather will allow him to travel back to the mountain. Now, the dogs must struggle against the elements to survive as they attempt to make their way back home.